2010
DOI: 10.1002/crat.201000378
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐ and microcrystals of doped niobates

Abstract: A Fergusonite-type phase of acceptor-doped lanthanum ortho-niobate La 1-x A x NbO 4 (A = Ca, Mg or Sr) has been synthesised by molten salt synthesis route. The high temperature behaviour and microstructure of samples doped by magnesium, calcium and strontium have been studied. The high temperature X-ray diffraction measurements in the temperature range from room temperature to 700 °C has been carried out. The scanning electron microscopy has been used to determine the samples microstructure and to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Ã and Acc ½ : The TG data presented in Fig. 8 show weak temperature dependency, and from previous studies for calcium-doped lanthanum orthoniobate, there is no indication of any phase segregation with temperature [23,25]. As calcium has a stable 2?…”
Section: Resultssupporting
confidence: 50%
“…Ã and Acc ½ : The TG data presented in Fig. 8 show weak temperature dependency, and from previous studies for calcium-doped lanthanum orthoniobate, there is no indication of any phase segregation with temperature [23,25]. As calcium has a stable 2?…”
Section: Resultssupporting
confidence: 50%
“…The LMNO agglomerates are quite large; their size reaches approximately 10 µm. This fact is in agreement with previous studies of sintered LMNO samples published elsewhere which proved that in the case of sintered samples prepared from MSS powders grains tend to agglomerate [11]. On the other hand the CTF grains are not so strongly agglomerated and have average sizes of 3-5 µm.…”
Section: Resultssupporting
confidence: 93%
“…The La 0 98 Mg 0 02 NbO 4 powder was prepared by the molten salt synthesis method (MSS) which was described elsewhere [11]. In order to produce composite samples the powders of CTF and LMNO were mixed in weight ratio 1:1 and then milled in an agate mortar.…”
Section: Methodsmentioning
confidence: 99%
“…The 021 and 040 reflections were chosen for detailed analysis because the first one is the strongest peak for LaNbO 4 while the other corresponds to this crystal direction along which the fast crystal growth has been observed before. 15 Table II presents widths (FWHM) of these reflections for the samples prepared in different conditions.…”
Section: Lanthanum Niobatementioning
confidence: 99%
“…13 14 Our previous investigation has shown that also selected proton conducting oxides can be successfully synthesized by MSS method. For example, magnesium-doped lanthanum niobate 15 and yttrium-doped barium cerate 16 obtained with the molten salt synthesis have been studied.…”
Section: Introductionmentioning
confidence: 99%